Left Atrial Size and Long‐Term Risk of Recurrent Stroke After Acute Ischemic Stroke in Patients With Nonvalvular Atrial Fibrillation. Issue 8 (15th August 2017) - Ogata, Toshiyasu; Matsuo, Ryu; Kiyuna, Fumi; Hata, Jun; Ago, Tetsuro; Tsuboi, Yoshio; Kitazono, Takanari; Kamouchi, Masahiro; ,
Abstract : Background: Among patients with ischemic stroke and atrial fibrillation, which ones are at high risk of recurrent stroke is unclear. This study aimed to determine whether left atrial size was associated with long‐term risk of stroke recurrence in patients with nonvalvular atrial fibrillation. Methods and Results: In this multicenter prospective cohort study, nonvalvular atrial fibrillation patients hospitalized for acute ischemic stroke were enrolled and followed up after discharge. Indexed‐left atrial diameter was obtained by dividing left atrial diameter by body surface area. Cause‐specific and subdistribution hazard ratios of recurrent stroke were estimated by Cox proportional hazards and Fine–Gray models, respectively. Risk prediction was evaluated by integrated discrimination improvement and net reclassification improvement. In total, 1611 patients (77.8±10.2 [mean±SD] years, 44.5% female) were included. During follow‐up for 2.40±1.63 (mean±SD) years, 251 patients had recurrent stroke and 514 patients died. An increased indexed‐left atrial diameter (per 1 cm/m 2 ) was significantly associated with elevated risk of stroke recurrence (hazard ratio 1.60, 95% CI 1.30–1.98). The association was maintained when death was regarded as the competing risk and in 1464 patients who were treated with anticoagulants (hazard ratio 1.59, 95% CI 1.27–2.00). Risk prediction for recurrent stroke was significantly improved by adding indexed‐left atrial diameter to the baseline model composed of the factors in the CHADS2 score or those in the CHA2 DS2 ‐VASc score. Conclusion: These findings suggest that left atrial enlargement is associated with an increased risk of recurrent stroke in nonvalvular atrial fibrillation patients with ischemic stroke.